Qatar : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper assesses efficiency of Qatar public investment. It discusses the trends in public capital spending and the rationale for improving public investment efficiency. The paper outlines three alternative methods for analyzing efficiency, and presents the main results. The results suggest that the efficiency of Qatar public investment spending is broadly comparable to GCC peers, but could be improved further. It is also concluded that strengthening fiscal institutions, particularly with an integrated public investment management process and a medium-term fiscal policy framework, is the key for improving public investment efficiency in Qatar.